(untitled) (Journal Of Educational and Psychological Researches, 2024)
The study aims to identify the requirements for the application of modified physical education in light of the quality of the educational process in the schools of Sultanate Oman. The questionnaire was applied to an exploratory sample of 40 physical education teachers in the Ministry of Education. The study recommends the need to develop a curriculum for modified physical education according to the best international specifications, work to follow up on developments and sports modifications for modified physical education and benefit from them, and hold workshops and training courses to refine the experiences of modified physical education teachers